Analisis implikasi Etika Administrasi Publik dalam Praktik Jual Beli Data Warga untuk Pemilu : Tinjauan terhadap Praktik Jual Beli Data Warga sebagai Tantangan Etis - Hasbana, Adinda Najwa; Nurizma, Alifia; Gerda Dewanti, Ardeta Naafi; Budi, Kusnar (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the ethical implications of public administration in the practice of buying and selling citizen data for general election purposes (Pemilu). A review was conducted of the practice of buying and selling citizens' data as an ethical challenge that can affect integrity and transparency in public administration. Through a qualitative approach, this research investigates the extent to which these practices can threaten the ethical principles of public administration, especially those related to privacy, security and fairness. It is hoped that the research findings will provide in-depth insight into the impact of the practice of buying and selling citizen data on ethical values ​​in the context of public administration. The implications of this research can be used as a basis for formulating more effective ethical guidelines in managing citizen data, especially in the context of election preparation and implementation.